1981
DOI: 10.1136/bjo.65.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Aging and degeneration of the human macula. 1. Outer nuclear layer and photoreceptors.

Abstract: SUMMARY In a light microscopic study of the macula of 104 human eyes obtained at necropsy of patients aged 3 to 96 we found: (1) Displacement of nuclei from the outer nuclear layer into the outer plexiform layer occurred in small numbers early in life and markedly increased after age 30.(2) Displacement of nuclei from the outer nuclear layer to the layer of rods and cones was rare in early life but increased considerably after age 40. (3) Displacement of nuclei is probably secondary to shrinkage of their attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
88
1
2

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(104 citation statements)
references
References 4 publications
10
88
1
2
Order By: Relevance
“…Marshall et al (1979) demonstrated a change with ageing in human photoreceptors, starting at the age of 40 years. Gartner & Henkind (1981) found that nuclei of photoreceptors from the outer nuclear layer were displaced into both the outer plexiform layer (increasing after 30 years of age and most pronounced after 50 years of age), and the layer of rods and cones (after 40 years of age and most commonly after 50 years of age). van Norren & van Meel (1985), who investigated the density of human cone pigments as a function of age, could not find any significant change in density up to 50 years of age.…”
Section: Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Marshall et al (1979) demonstrated a change with ageing in human photoreceptors, starting at the age of 40 years. Gartner & Henkind (1981) found that nuclei of photoreceptors from the outer nuclear layer were displaced into both the outer plexiform layer (increasing after 30 years of age and most pronounced after 50 years of age), and the layer of rods and cones (after 40 years of age and most commonly after 50 years of age). van Norren & van Meel (1985), who investigated the density of human cone pigments as a function of age, could not find any significant change in density up to 50 years of age.…”
Section: Ageingmentioning
confidence: 99%
“…Weale (1963), who originally ascribed the major portion of age-related VF DLS loss to preretinal factors, later suggested that the cell loss within the central optic pathway is the major factor in the age-related decline in sensitivity (Weale 1983). Many histological studies have shown that age-related reductions in photoreceptor density (Marshall et al 1979;Gartner & Henkind 1981;Dorey et al 1989;Gao & Hollyfield 1992;Curcio et al 1993), photopigment density (van Norren & van Meel 1985;Kilbride et al 1986), the number and morphology of optic nerve axons (Dolman et al 1980;Balazsi et al 1984;Sommer et al 1984;Repka & Quigley 1989) and the population density of neurons in the visual cortex (Devaney & Johnson 1980) do exist. Several studies have assumed a linear decrease in threshold values with age (Drance et al 1967a(Drance et al , 1967bEgge 1984;Flammer 1985;Brenton & Phelps 1986;Haas et al 1986;Jaffe et al 1986;Heijl et al 1987;Zulauf et al 1994a;Koller et al 2001;Okuyama et al 2001;Heijl 2005), whereas many authors have described a non-linear mathematical model or found a change point, demonstrating an increasing loss of sensitivity at a specific age (Derefeldt et al 1979;Iwase et al 1988;Vivell et al 1992;Lachenmayr et al 1994Lachenmayr et al , 2001Adams et al 1999;Lorch et al 2001;…”
Section: Ageingmentioning
confidence: 99%
“…Earlier histopathologic studies in ageing eyes also indicated preferential rod damage with elongation and nuclear displacement starting at age 40 years. 5,6 Holopigian et al 7 investigated the peripheral cone and rod function in subjects with early ARM by obtaining dark-adaptation curves, electro-oculograms (EOG), and full-field electroretinograms (ERG). They found no difference for the cones compared to agematched controls but abnormal absolute thresholds and cone-rod break times as well as impaired electroretinographic measures in the full-field ERG for the rod system.…”
Section: Introductionmentioning
confidence: 99%
“…In the retina, loss and displacement of photoreceptor cell nuclei occur (Gartner & Henkind, 1981) together with convolution of the outer portion of rod photoreceptor outer segments (Marshall, Grindle, Ansell & Borwein, 1979). Morphological changes in cone photoreceptor cells which subserve high acuity vision do not appear to have been studied except for dark-adaptation thresholds of cones which rise threefold from ages 20 to 80 years (Gunkel & Gouras, 1963).…”
Section: Introductionmentioning
confidence: 99%